Teenage Pregnancy: Impact of the Integral Attention Given to the Pregnant Teenager and Adolescent Mother as a Protective Factor for Repeat Pregnancy - Maria José Carvalho Sant'Anna; Kepler Alencar Mendes Carvalho; Amanda Melhado; Verônica Coates; Hatim A. Omar (The Scientific World Journal)
The purpose of this study was to evaluate the impact of the integral attention to the health of pregnant adolescents and adolescent mothers, having follow-up from the Integral Support Program for the Pregnant Teen (ISPPT), with the intention to determine quality of life and prevent repeat pregnancy. A prospective study comprised 85 adolescents attended by the ISPPT between January 2002 and June 2006 who participated in meetings during pregnancy with a multidisciplinary team that provided orientation concerning family planning, self-esteem, pregnancy prevention, motivation to continue education and/or work, and evaluate the postpartum mother-child relationship. The following were analyzed: education level, marital status, contraceptive use, thoughts and attempts at abortion, repeat pregnancy. This study was approved by the Human Research Ethics Committee. The Epi-Info v6.0b software was used for data and result evaluation using the means and the chi-squared test. The mean age of the adolescents was 15.7 years, 3.52% had repeat pregnancy within a mean follow-up of 23 months after childbirth, the mean education level was 8.1 years, 30.5% dropped out of school, with 79.4% occurring before pregnancy, 64.6% used no contraceptives, 68.3% were single, and 81.3% had a positive role model. One year after birth, 67.5% studied, 50% worked, 55.1% lived with the partner, 77% correctly used contraceptives, every child lived with their mothers and their vaccinations were up to date. The results demonstrate that the global attention given to the health of adolescent mothers and pregnant adolescents is a protective factor for pregnancy relapse and quality of life.